2019
DOI: 10.1115/1.4044095
|View full text |Cite
|
Sign up to set email alerts
|

Using Contrast Motion to Generate Patient-Specific Blood Flow Simulations During Invasive Coronary Angiography

Abstract: Virtual fractional flow reserve (vFFR) is an emerging technology employing patient-specific computational fluid dynamics (CFD) simulations to infer the hemodynamic significance of a coronary stenosis. Patient-specific boundary conditions are an important aspect of this approach and while most efforts make use of lumped parameter models to capture key phenomena, they lack the ability to specify the associated parameters on a patient-specific basis. When applying vFFR in a catheter laboratory setting using X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As a water-soluble CORM, CORM-3 is an effective carrier to deliver CO and modulate many endogenous reactions [24,29]. In addition, many animal studies have found that CORMs have protective effects in the heart and lungs [30,31], including hyperacute endotoxic shock, pulmonary inflammation, postoperative ileus, airway hyperresponsiveness, and pulmonary hypertension [32][33][34][35].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…As a water-soluble CORM, CORM-3 is an effective carrier to deliver CO and modulate many endogenous reactions [24,29]. In addition, many animal studies have found that CORMs have protective effects in the heart and lungs [30,31], including hyperacute endotoxic shock, pulmonary inflammation, postoperative ileus, airway hyperresponsiveness, and pulmonary hypertension [32][33][34][35].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%